2015
DOI: 10.1017/jmo.2014.72
|View full text |Cite
|
Sign up to set email alerts
|

Organisational sequestering of workplace bullying: Adding insult to injury

Abstract: This paper explores empirical data from human resources practitioners and employees to define the ways in which organisations respond to complaints about workplace bullying in New Zealand. Despite recommendations that organisations take workplace bullying seriously and increasing research in recent years, little evidence exists of improvements in the management of this problem. Indeed, this study adds to the gloom by providing an account of the ways in which a group of organisations failed to take responsibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…But at the same time, it is difficult to do the HR planning in such situation because of vague boundaries and differences among HR roles, dubious definitions and norms for conduct to be regarded as WB, and also insufficient organizational policies to handle it (Fox & Cowan, 2015). The difficulties faced by HRD professionals in WB situations were also observed by Thirlwall (2014). His interviewees reported that organizational sequestering prolonged the bullying and created additional problems for them.…”
Section: What Recent Wb Research Concludesmentioning
confidence: 88%
“…But at the same time, it is difficult to do the HR planning in such situation because of vague boundaries and differences among HR roles, dubious definitions and norms for conduct to be regarded as WB, and also insufficient organizational policies to handle it (Fox & Cowan, 2015). The difficulties faced by HRD professionals in WB situations were also observed by Thirlwall (2014). His interviewees reported that organizational sequestering prolonged the bullying and created additional problems for them.…”
Section: What Recent Wb Research Concludesmentioning
confidence: 88%
“…Existing studies have found that when employees trust organizational members more, they will have higher PS (Thirlwall, 2015;Koopmann et al, 2016;Arnetz et al, 2019a). Employees (especially new hires) who suffer WB such as being given an excessive workload, tend to highly distrust their bullies (Thirlwall, 2015;Logan and Malone, 2018). Such a low level of trust will reduce the PS of employees.…”
Section: The Mediating Effect Of Psychological Safetymentioning
confidence: 99%
“…Following from the above, organisational commitment to eliminating the problem of workplace bullying is a critical factor. Indeed, even alongside the call for legislation in countries where regulation is lacking, it is not surprising to observe the emphasis on ensuring the appropriateness of workplace culture (D’Cruz, 2018; D’Cruz and Noronha, 2010; Thirlwall, 2015). Moreover, though sanctions by the state’s administration are necessary to ensure compliance (Hoel and Einarsen, 2010), the effectiveness of the mechanisms thus put in place depends on the attitudes of the management (Hanley and O’Rourke, 2016).…”
Section: Discussionmentioning
confidence: 99%